Investigating Accessibility Barriers in Software Development Tools Through the Blind People's Perspective - Melo, Giselle Lorrane Nobre; dos Santos, Suzane Santos; Teran, Luciano Arruda; Monteiro, Ingrid Teixeira; Rodrigues, Kamila da Hora Rios; Mota, Marcelle Pereira (Anais do Simpósio Brasileiro de Sistemas Colaborativos (SBSC); 2026: Anais do XXI Simpósio Brasileiro de Sistemas Colaborativos, 2026)
Even when using screen reader tools, blind software developers face digital accessibility issues in collaborative work. Our primary goal was to investigate the difficulties faced by software developers, specifically in team integration and communication with professional tools. For that, we carried out a Rapid Literature Review (RLR) and an accessibility inspection using the Semiotic Inspection Method mediated by Screen Reader (SIM-SR) to investigate the communicability of task management tools and of instructions as coordination tools in the 3C collaboration model. As a result, we proposed 16 collaborative work considerations to the equity of blind people in software teams and to improve their daily development experiences mediated by management tools.